Protocol to study how expectations guide predictive eye movements and information sampling in humans - Annika Garlichs; Mark Lustig; Matthias Gamer; Helen Blank (STAR Protocols)
Summary: Investigating eye movements provides a unique tool to explore how expectations influence information sampling in the visual domain. Here, we present a protocol for measuring predictive eye movements during face anticipation as well as fixations and dwell time during face recognition in humans. We describe steps for setting up two eye-tracking experiments. We then detail procedures for the measurement and analysis of eye-tracking data.For complete details on the use and execution of this protocol, please refer to Garlichs et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.